Financial statement fraud: evidence from Malaysian public listed companies / Norziaton Ismail Khan and Arfa Aqila Muhammad Hapiz - Ismail Khan, Norziaton; Muhammad Hapiz, Arfa Aqila (Universiti Teknologi MARA, Perlis, 2022)
Financial statement fraud is seen as a rampant problem around the world. Early detection is one of the ways to curb financial statement fraud, and it has motivated this study to be conducted. The main objective of this study is to investigate the primary factors that influence the public listed companies in Malaysia to be involved in financial statement fraud. The sample used in this study comprised 40 financial statement fraud companies matched with another 40 non-financial statement fraud companies listed in Bursa Malaysia from 2003 to 2020. This study used the fraud triangle theory to form the research framework and develop the research hypotheses. Four hypotheses based on the elements of fraud, which are the financial target, external pressure, earnings management, and related-party transaction, have been developed and tested. Regression analysis was conducted to examine the relationship between the elements of fraud and financial statement fraud. The results indicated that there is a significant relationship between financial targets, earnings management, related-party transaction and financial statement fraud, thus the hypotheses are accepted. However, there is an insignificant relationship between external pressure and financial statement fraud, hence the hypothesis was rejected. Interestingly, it was found that the fraud companies had poorer earnings quality one year before they committed the financial statement fraud. Overall, this study would assist the auditors as it identifies early warning signals or red flags. Information obtained from this study could be used by Bursa Malaysia to develop strong regulations and encourage Malaysian public listed companies to enhance anti-fraud policies.